Transcriptome analysis provides insights into the role of TLP16 in Musa acuminata Resistance to Fusarium oxysporum f. sp. cubense wilt - Yi-le Huo; Si-wen Liu; Huo-qing Huang; Zai-yuan Li; Mudassar Ahmad; Meng-xia Zhuo; Wen-juan Chen; Chun-yu Li; Bo Liu; Ya-dong Li (BMC Plant Biology)
Abstract Background Thaumatin-like proteins (TLPs) are crucial pathogenesis-related proteins that significantly contribute to plant defense rection. Fusarium oxysporum f. sp. cubense (Foc) causes Fusarium wilt of bananas, a serious threat to global production. However, the role of TLPs in disease resistance remains unclear. Results This study identified 49 TLP genes in banana, predominantly localized in the extracellular space, and distributed across 11 chromosomes. The ancestor–descendant relationship was explained, six genes remained remarkably conserved across species could represent the ancestral genes of the TLP gene family. Promoter regions, transcriptome and qRT-PCR analysis suggested that MaTLP16 might be involved in disease resistance. Furthermore, transcriptional silencing of MaTLP16 resulted in more severe leaf damage compared to the control, indicating that MaTLP16 is an important Foc resistance-related gene. Conclusion This study conducted a comprehensive genome-wide identification and systematic analysis of the TLP gene family in bananas. Our findings establish a foundation for further functional studies of MaTLP genes and highlight MaTLP16 as a strong candidate for use in breeding programs aimed at enhancing resistance to Musa diseases.